Mutu Fisik dan Mutu Kimia Sabun Padat dengan Variasi Konsentrasi Ekstrak Kunyit (Curcuma domestica) - wuryandari, wahyu; Firnanda, Andreas Candra (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
Turmeric (Curcuma domestica) contains curcumin which can provide antioxidant and antibacterial activity. Curcumin can also be used as a natural brownish yellow dye at alkaline pH, so it can be used as an additional ingredient in making solid soap. This research aims to determine the physical quality a chemical quality of solid soap preparations with varying concentrations of turmeric extract. This research includes descriptive research which includes making turmeric extract, making solid soap with varying concentrations of turmeric extract concentration of 2 gram (F1), 3 gram (F2) and 4 grams (F3) as well as physical quality testing which includes organoleptic, water content, foam stability and chemical quality testing include pH, fee alkali and free fatty acids. The results of the physical quality test of the 3 soaps formulation were brown soap, solid and odourless. Water content for F1: 0,6486%, F2: 0,4897%, F3: 0,5228%. Foam stability for F1: 5,5 cm, F2: 5,3 cm, F3: 5,3 cm. The chemical quality test result for pH are F1: 8,54, F2: 8,81, F3: 8,94 while free alkali for F1: 0,0428%, F2: 0,0429% dan F3: 0,0461%. Based on the research that has been carried out, it can be conclude that the three solid soap formulas with varying concentrations of turmeric extract have content, foam stability, pH and free alkali in accordance with SNI-3532-2016.